Pregnancy toxaemia prevention by feeding Sarda ewes a specific herbal extract compound - Ronchi B.; Molina Casanova A.M.; Bernabucci U.; Giacinti G.; Rosati R. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
Some herbal extracts were shown to be useful in human and veterinary medicine in preventing or alleviating metabolic disorders and their consequences. The aim of the present study was to evaluate the effects of a herbal extract compound supplementation for pregnancy toxaemia (PT) prevention in dairy ewes. Thirtythree pregnant and multiparous dairy ewes were monitored during the last 40 days of pregnancy and the first 30 days in milk. The diet was given as total mixed ration and it was the same for all animals. The 33 subjects were randomly assigned to two groups, which were balanced for expected lambing date and body condition score. The treated group, consisting of 22 heads, was supplemented with 10 g/head/d of Enerphyt-Plus (Biorama, Rogeno, Milano, Italy). The remained 11 ewes were used as control group. Enerphyt-Plus was added into the total mixed ration and the treatment lasted until lambing event. Blood samples were taken and body condition score was registered during the peripartum period at 7 d intervals. Number of lambs born per ewe was recorded at lambing. Glucose, non-esterified fatty acids (NEFA), beta-OH butyrate (BHBA), and urea concentrations, as well as ?- glutamil transferase (GGT) and aspartate amino transferase (AST) activities were determined on plasma samples. Between groups, no differences were found for number of lambs born per ewe. Treated ewes showed higher (P < 0.05) glucose, lower (P < 0.05) NEFA, BHBA and GGT around lambing. Results of the present study demonstrated that the supplementation with a specific formulated phyto-derivate product was able to improve energy metabolism and liver function of periparturient dairy ewes. The reduction of PT risk in periparturient dairy ewes can have positive effects on animal welfare and performances.
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)